A Conceptual Framework for Learning Management Accounting1. (March 2014) - Spraakman, Gary; Jackling, Beverley
Abstract This paper demonstrates how Schoenfeld's (1985) conceptual framework for mathematics can provide an alternate framework for learning and thereby teaching management accounting. The four‐part framework—heuristics, resources, beliefs, and controls—is a refinement to problem‐based learning with three attributes in regard to management accounting. First, all aspects for teaching management accounting are integrated into a single framework or theory. Consistency among all parts of management accounting clarifies student and instructor roles in the learning process. Second, the framework's problem‐solving focus with linkages to explanatory materials or resources allows students to be rigorously informed about the functionality of management accounting heuristics. Third, transition or extension of relatively simple, standard problems to more complex nonstandard problems or cases is facilitated by introducing appropriate beliefs and controls. In effect, this approach enables management accounting, and particularly case analysis, to be taught with more structure.